2011
DOI: 10.1007/978-1-61779-108-6_19
|View full text |Cite
|
Sign up to set email alerts
|

Raman Micro-Spectroscopy as a Non-invasive Cell Viability Test

Abstract: The number of techniques to identify, quantify and characterise cell death is rapidly increasing as more is known about the complex mechanisms underlying this process. However, most of these techniques are invasive and require preparation steps such as cell fixation, staining or protein extractions. Non-invasive analysis of living cells represents a key point in cell biology, e.g. in toxicology studies or in tissue engineering. In this chapter, we report the usefulness of Raman spectroscopy as a non-invasive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…The characteristic peaks are assigned in Table (Table S1) based on previous studies involving several cell lines and biomolecules. 31-36 Figure 2 and Figure S3 shows that the Raman spectra profile of treated groups were decreased after 24h, which mainly reflected in those Raman bands assigned to nucleic acid: 794 cm -1 (DNA), 941cm -1 (RNA), 1092 cm -1 (DNA), 1375 cm -1 (A, G, T) 1579 cm -1 (DNA). The changes at 48h shown in figure S1 were similar to those at 24h.…”
Section: Resultsmentioning
confidence: 98%
“…The characteristic peaks are assigned in Table (Table S1) based on previous studies involving several cell lines and biomolecules. 31-36 Figure 2 and Figure S3 shows that the Raman spectra profile of treated groups were decreased after 24h, which mainly reflected in those Raman bands assigned to nucleic acid: 794 cm -1 (DNA), 941cm -1 (RNA), 1092 cm -1 (DNA), 1375 cm -1 (A, G, T) 1579 cm -1 (DNA). The changes at 48h shown in figure S1 were similar to those at 24h.…”
Section: Resultsmentioning
confidence: 98%
“…In an effort to quantify cell viability non-invasively, Notingher et al 67 69 used spontaneous Raman spectroscopy to distinguish between live and dead cells and also found that the stage of the cell cycle that particular cells were in could be determined primarily by changes in peaks attributed to DNA at 782, 788 and 1095 cm −1 . Dead cells had particularly low intensity DNA peaks and also alterations in protein peaks, thought to be due to changes in protein conformation.…”
Section: Applications Of Raman Spectroscopy To Regenerative Medicinementioning
confidence: 99%
“…Another class of contributors to the spectral outcome is the instrumental settings. The laser wavelength, numerical aperture of the microscope objective, the use of a high-speed encoded stage (HSES), laser power, laser exposure time, and its focus adjustment are the main instrumental parameters, most of which affect the signal intensity and pattern. …”
Section: Spectral Reproducibilitymentioning
confidence: 99%